PENGARUH PERPUTARAN KAS, PIUTANG DAN PERSEDIAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI INDEKS SAHAM SYARI'AH INDONESIA PADA TAHUN 2019-2024 - Wulan Sari Dwi Wahyuni; Addiarrahman Addiarrahman (Yayasan Nusantara Hasana Berdikari, 2026)
Profitability is one of the main indicators in assessing a company's financial performance. Efficiency in managing working capital, especially cash turnover, receivables and inventory plays a major role in increasing profitability. The pharmaceutical industry experienced significant dynamics during the 2019-2024 period, especially since the Covid-19 pandemic. Despite the increase in demand for pharmaceutical products, not all companies showed an increase in profitability. Several companies experienced an increase in cash turnover or receivables but were not followed by an increase in Return On Assets (ROA) which indicated a mismatch between operational efficiency and financial performance. This study aims to determine how cash turnover, receivables and inventory affect profitability in pharmaceutical companies. The sample used in this study was 6 pharmaceutical companies. The type of data used is secondary data. Data processing using Eviews. The data analysis technique used is panel data regression analysis. The results of the study showed that cash turnover, receivables and inventory partially or simultaneously do not have a significant effect on profitability. In testing the classical assumption with a normal distribution, there were no symptoms of heteroscedasticity and multicollinearity.